2015
DOI: 10.1007/s00421-014-3094-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycogen reduction on cardiorespiratory and metabolic responses during downhill running

Abstract: PurposeExercise induced muscle damage and lowered glycogen are common during heavy training periods, and may prolong recovery. We examined the effects of lowered glycogen on cardiorespiratory, metabolic and perceptual responses to downhill running. AQ1 MethodsTwelve men performed two downhill runs (−12 % gradient, 12.1 ± 1.1 km h ) separated by 6 weeks, under normal (NORM) and reduced glycogen (RED) conditions in a crossover design. For RED, participants performed exhaustive cycling at 60 % O power (95 ± 13 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…For instance, HR values were significantly higher over time (from +9.3 to +12.6%, Figure 4E ) that might be related to the VO 2 drift but also, to the potential increase of core body temperature experienced during DHR ( Westerlind et al, 1992 ). Time course of RE responses during DHR are relatively scarce in literature ( Dick and Cavanagh, 1987 ; Gavin et al, 2015 ; Westerlind et al, 1992 ), with no reports in trained runners accustomed to eccentric work. In the current investigation, we reported a 5.3–6.8% increase in RE (Figure 4B ) at the end of DHR for both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HR values were significantly higher over time (from +9.3 to +12.6%, Figure 4E ) that might be related to the VO 2 drift but also, to the potential increase of core body temperature experienced during DHR ( Westerlind et al, 1992 ). Time course of RE responses during DHR are relatively scarce in literature ( Dick and Cavanagh, 1987 ; Gavin et al, 2015 ; Westerlind et al, 1992 ), with no reports in trained runners accustomed to eccentric work. In the current investigation, we reported a 5.3–6.8% increase in RE (Figure 4B ) at the end of DHR for both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, internal exercise load has been shown to increase after hard endurance training and competition, representing an augmented internal load and decreased performance [4,6]. This phenomenon could be affected by several psychophysiological and metabolic factors such as rate of perceived exertion (RPE), glycogen depletion, heart rate, dehydration, and exercise-induced muscle damage (EIMD) [3,5,[7][8][9][10]. Therefore, monitoring of internal load may reveal the state of fatigue of an athlete and determine a method for systematically quantifying the exercise dose (i.e., work completed), as well as the individual response to training stimulus [11,12] that might act as a guide in the search for different strategies aimed at decreasing it [11].…”
Section: Introductionmentioning
confidence: 99%
“…19 Familiarization one involved an incremental cycling trial, with participants cycling (Excalibur Sport 925900, Lode, Groningen, The Netherlands) at ~75 rpm for 3 min at 50 W; Familiarization two involved a submaximal, incremental treadmill run (Pulsar, h/p/cosmos Sports & Medical GmbH, Germany) to establish individual downhill running speed (based upon lactate threshold). 20 The run began at 8 km•h -1 (1% gradient), followed by 1 km•h -1 increments every 4 min until volitional exhaustion (the point at which the participant felt they could no longer continue), or eight stages were completed. Fingertip blood (25µL) samples were drawn from the right index finger, with the pronated hand resting on the treadmill handrail.…”
Section: <<< Insert Figure 1 Here >>>mentioning
confidence: 99%
“…For the LOW condition, participants then cycled at 60% O 2max power (~75 rpm; workload, 181 ± 40 W) until volitional exhaustion (time, 95 ± 13 min; blood glucose reduced by -1.47 ± 0.56 mmol•L -1 (-31.8%)). 20 Biopsy studies have shown this protocol to be effective for depleting muscle glycogen (reduction: total muscle, -77%, type I fibers, -95%, type II fibers, -70%). 21,22 For the NORM condition, participants completed a 2 h seated quiet rest, with no change in blood glucose values.…”
Section: Experimental Sessionsmentioning
confidence: 99%
See 1 more Smart Citation